Performance assessment of low-cost environmental monitors and single sensors under variable indoor air quality and thermal conditions. (January 2021) - Demanega, Ingrid; Mujan, Igor; Singer, Brett C.; Anđelković, Aleksandar S.; Babich, Francesco; Licina, Dusan
Abstract: Recent technological advancements have enabled the development and deployment of low-cost consumer grade monitors for ubiquitous and time-resolved indoor air quality monitoring. With their reliable performance, this technology could be instrumental in enhancing automatic controls and human decision making. We conducted a comprehensive performance evaluation of eight consumer grade multi-parameter monitors and eight single-parameter sensors in detecting particulate matter, carbon dioxide, total volatile organic compounds, dry-bulb air temperature, and relative humidity. In the controlled chamber, we generated eight air pollution sources, each at two thermodynamic conditions — cool and dry (20 ± 1 °C, 30 ± 5%), and warm and humid (26 ± 1 °C, 70 ± 5%). The majority of tested devices under-reported reference particle measurements by up to 50%, provided acceptable responses for carbon dioxide within 15% and diverging results with poor quantitative agreement for total volatile organic compounds. Despite the reported disparities in quantitative agreements, most of the low-cost devices could detect source events and were strongly correlated with the reference data, suggesting that these units could be suitable for measurement-based indoor air quality management. Most of the tested devices have also proven to competently measure air temperature (within+/-0.6 °C) and relative humidity (within+/-5% RH) and maintained a stable measurement accuracy over the two thermodynamic conditions. Highlights: We evaluated 8 low-cost environmental monitors and 8 single sensors in 2 distinct seasons. Most of the tested units can be used for measurement-based IAQ and comfort management. Awair 2 nd Edition scored highest overall accuracy in measuring multiple environmental parameters among the low-cost units. Air pollution source type affects monitor accuracy while seasonal impact is not obvious. Price of the low-cost monitors does not scale with their performance.